DESIGN OF ARRAY FED BEAM REFLECTOR ANTENNA WITH MAXIMUM POWER RADIATED EFFICIENCY BASED ON NEAR FIELD PATTERN SYNTHESIS USING SUPPORT VECTOR MACHINE (International Journal of Food and Nutritional Sciences, 2023)
ABSTRACT: Radiation efficiency is one of the important parameter to describe how efficiently an antenna transmits and receives RF signals, which is defined as the ratio of the total power radiated by an antenna to the total input power received from the generator. The maximum radiation efficiency can be obtained when the feed array excitation of a reflector antenna is synthesized by the Conjugate Field Matching (CFM) method. However, the CFM method only get the strongly tapered feeding power distribution. This can lead to most of Power Amplifiers (PAs) working in low efficiency states and reduce the Equivalent Isotropic Radiated Power (EIRP) with the limited power consumption. Hence in order to solve these issues, design of array fed beam reflector antenna with maximum power radiated efficiency based on near field pattern synthesis using Support Vector Machine is presented. In this work, combining the radiation efficiency and the PA efficiency, the radiated power efficiency (RPE) is defined as the new design goal and is to be raised to achieve higher EIRP. For this reason, a method based on the near-field pattern synthesis is described. In this method, all the ON-state PAs are required to work in the highest efficiency state. Then, with well trained Support Vector Machine (SVM), the ON–OFF states of the PAs are adjusted so that the reflected focal field can be better synthesized by the near-field pattern of the feed array. Thus, the loss of the radiation efficiency will be minimized. As a result, RPE will be improved.